AKSELERASI DIGITAL MARKETING DAN ENGAGEMENT PELANGGAN DENGAN SOAR: STUDI KASUS PT CAPELLA MULTIDANA CABANG NIBUNG RAYA - Chairiyah, Hasanatul; Sulistya Rini, Endang; Tryana Sembiring, Meilita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Competition in the financing industry pushes companies to be more proactive in using digital channels for marketing and customer communication. However, not every company succeeds in doing so. PT Capella Multidana Nibung Raya Branch, a financing company has been using Instagram as a marketing platform, yet its digital channel contributes only 10% to total sales, with an engagement rate of just 0.7%, which falls below the financing industry average of above 1%. This study aims to analyze the factors behind the low effectiveness of digital marketing and to formulate an acceleration strategy based on the SOAR framework (Strengths, Opportunities, Aspirations, Results). Using a qualitative case study approach, data was collected through in-depth interviews, observation of digital activities, content analysis, and marketing reports. The findings reveal that the branch has notable strengths, including a solid reputation, a strong showroom network, and high customer trust, but these have not been fully leveraged. Contributing factors include the absence of dedicated digital marketing staff, a lack of clearly defined digital KPIs, and inconsistent digital content management. The study proposes several strategies: establishing a digital marketing coordinator role, optimizing social media platforms, and improving digital collaboration with showrooms and agents.